Madonna and child the development of Christian symbolism. (Dallas, Tex. Swan / Jones Productions, 1992)
Traces the origins and meaning of Christian symbols in Medieval culture and discusses changes -- artistic, historic & theological -- that influenced them. Focuses on the Incarnation cycle, including the Christmas story.
VHS format.
Written by Lois Swan Jones ; directed by Preston Jones ; introduction by Larry Gleason.
Jeffrey Swan Jones.
Keywords: Christian art and symbolsim -- Medieval, 500-1500.; Sculpture, Medieval; Jesus Christ--Art.; Mary, Blessed Virgin, Saint?Art.